USING PORTFOLIO ASSESSMENT TO ENHANCE STUDENTS' SCIENCE PROCESS SKILLS IN STEM LEARNING ACTIVITIES - Shidiq, Galih Albarra; Bunnaen, Wutthisak; Widiyan, Agung Purwa (Universitas Tanjungpura, 2024)
Using portfolio assessment to enhance students